Technology development of a maximum power point tracker for regenerative fuel cells - Jansen van Rensburg, Neil (My University, 2015)
Global warming is of increasing concern due to several greenhouse gases. The combustion of fossil fuels is the major contributor to the greenhouse effect. To minimalise this effect, alternative energy sources have to be considered. Alternative energy sources should not only be environmentally friendly, but also renewable and/or sustainable. Two such alternative energy sources are hydrogen and solar energy. The regenerative fuel cell, commonly known as a hydrogen generator, is used to produce hydrogen. The current solar/hydrogen system at the Vaal University of Technology’s Telkom Centre of Excellence makes use of PV array to supply power to an inverter and the inverter is connected to the hydrogen generator. The inverter provides the hydrogen generator with 220VAC. The hydrogen generator has its own power supply unit to convert the AC power back to DC power. This reduces the efficiency of the system because there will be power loss when converting DC power to AC power and back to DC power. The hydrogen generator, however, could be powered directly from a PV array. However, the hydrogen generator needs specific input parameters in order to operate. Three different input voltages with their own current rating are required by the hydrogen generator to operate properly. Thus, a DC-DC power supply unit needs to be designed to be able to output these parameters to the hydrogen generator. It is also important to note that current PV panel efficiency is very low; therefore, the DC-DC power supply unit also needs to extract the maximum available power from the PV array. In order for the DC-DC power supply unit to be able to extract this maximum power, a maximum power point tracking algorithm needs to be implemented into the design. The DC-DC power supply is designed as a switch mode power supply unit. The reason for this is that the efficiency of a switch mode power supply is higher than that of a linear power supply. To reach the objective the following methodology was followed. The first part of the research provided an introduction to PV energy, charge controllers and hydrogen generators. The problem statement is included as well as the purpose of this research and how this research was to be carried out. The second part is the literature review. This includes the background study of algorithms implemented in MPPT’s; it also explains in detail how to design the MPPT DC-DC SMPS. The third part was divided into two sections. The first section is the design, programming and manufacturing of the MPPT DC-DC SMPS. The second section is the simulation of the system as a whole which is the simulation of the PV array connected to the MPPT DC-DC SMPS and the hydrogen generator. The fourth part in the research compared the results obtained in the simulation and practical setup. The last part of the research provided a conclusion along with recommendation made for further research. The simulation results showed that the system works with an efficiency of 40,84%. This is lower than expected but the design can be optimised to increase efficiency. The practical results showed the efficiency to be 38%. The reason for the lower efficiency is the simulation used ideal components and parameters, whereas the practical design has power losses due to the components not being ideal. The design of the DC-DC switch mode power supply, however, indicated that the hydrogen generator could be powered from a PV array without using an inverter, with great success.
M. Tech. (Department of Electronic Engineering, Faculty of Engineering and Technology) --Vaal University of Technology|
Keywords: Alternative energy sources; Hydrogen energy; Solar energy; Regenerative fuel cell; Hydrogen generator; PV array; Photovoltaic array; Maximum power point tracking algorithm; 621.312429; Fuel cells; Hydrogen as fuel